Experimental estimation of tungsten impurity sputtering due to Type I ELMs in JET-ITER-like wall using pedestal electron cyclotron emission and target Langmuir probe measurements. (8th January 2016) - Guillemaut, C; Jardin, A; Horacek, J; Borodkina, I; Autricque, A; Arnoux, G; Boom, J; Brezinsek, S; Coenen, J W; De La Luna, E; Devaux, S; Eich, T; et al.
Abstract: The ITER baseline scenario, with 500 MW of DT fusion power and Q = 10, will rely on a Type I ELMy H-mode and will be achieved with a tungsten (W) divertor. W atoms sputtered from divertor targets during mitigated ELMs are expected to be the dominant source in ITER. W impurity concentration in the plasma core can dramatically degrade its performance and lead to potentially damaging disruptions. Understanding the physics of the target W source due to sputtering during ELMs and inter-ELMs is important and can be helped by experimental measurements with improved precision. It has been established that the ELMy target ion impact energy has a simple linear dependence with the pedestal electron temperature measured by Electron Cyclotron Emission (ECE). It has also been shown that Langmuir Probes (LP) ion flux measurements are reliable during ELMs due to the surprisingly low electron temperature. Therefore, in this paper, LP and ECE measurements in JET-ITER-Like-Wall (ILW) unseeded Type I ELMy H-mode experiments have been used to estimate the W sputtering flux from divertor targets in ELM and inter-ELM conditions. Comparison with similar estimates using W I spectroscopy measurements shows a reasonable agreement for the ELM and inter-ELM W source. The main advantage of the method involving LP measurements is the very high time resolution of the diagnostic (∼10 μ s) allowing very precise description of the W sputtering source during ELMs.